Efficient Total Synthesis of (S)‐Dihydroresorcylide, a Bioactive Twelve‐Membered Macrolide. Issue 3 (1st March 2013) - Zhang, Li; Ma, Wenquan; Xu, Lili; Deng, Fei; Guo, Yuewei
Abstract The efficient synthesis of (S)‐dihydroresorcylide (1a) along with trans‐resorcylide dimethyl ether (2b), was achieved in linear 9 steps from commercially available orcinol monohydrate (6) with esterification, carbonylation, and ring‐closing metathesis (RCM) as the key steps in the synthetic sequence.